A systematic review of behaviour change techniques used in interventions to increase physical activity among breast cancer survivors - Hailey, Verity; Rojas-Garcia, Antonio; Kassianos, Angelos P. (My University, 2022)
Background Despite evidence that physical activity (PA) can help reduce recurrence and mortality, many breast cancer survivors are less active than recommended levels. The aim of this systematic review is to advance our understanding of which behaviour change techniques (BCTs) have been used in interventions promoting breast cancer survivors’ PA and to evaluate their potential to increase PA. Methods A systematic search was conducted in five databases (Medline; PsycInfo; Embase; CINAHL and Scopus) for studies published between 2005 and 2019. Following a rigorous screening process, 27 studies were retained. These were reviewed and analysed for quality, coded for BCTs (k = 0.65) and interventions categorised according to their potential to increase PA using an established methodology. Results The majority of studies were moderate quality (64%). Demonstration on how to perform the behaviour was the most commonly used BCT (n = 23). Adding objects to the environment, (pedometer or accelerometer) was the BCT with the highest potential to increase PA. This was followed by, goal setting and self-monitoring of behaviour. A theory-based approach to evaluation was used in only 59% (n = 16) of the studies. Conclusions The results of this review inform which BCTs have the potential to increase PA for breast cancer survivors and inform intervention development. Future research, is encouraged to properly report intervention procedures around dose and frequency of intervention components to allow for review and replication.
Keywords: Behaviour change techniques; Breast cancer; Exercise; Physical activity; Survivorship